PENDEKATAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PENCURIAN RINGAN PERSPEKTIF HUKUM ISLAM - satriadi Laupe (IAIN BONE, 2022)
AbstractThis article examines the restorative justice approach in resolving the crime of minor theft in the view of Islamic law. This research is a normative study and uses a qualitative descriptive analysis in explaining restorative justice crimes of minor theft in the view of Islamic law. The results of the study indicate that the crime of minor theft is one of the materials that becomes the object of resolving cases using a restorative justice system approach. Minor crimes that can be resolved by this route are Articles 363, 373,379,384, 407 and 482 of the Criminal Code with a loss value of not more than Rp. 2,500,000. The settlement of cases of minor theft crimes with a restorative justice approach is in line with the doctrine in Islamic law with settlements through the path of peace and wisdom. The restorative settlement is carried out provided that peace has begun between the perpetrator, the victim, the perpetrator's family and community leaders in litigation with or without compensation.Keywords: Criminal act; Islamic law; Minor Theft; Restorative justice.